Intravenous Ethanol Increases Dopamine Release in the Ventral Striatum in Humans: PET Study Using Bolus-Plus-Infusion Administration of [11C]raclopride. Issue 3 (March 2015) - Aalto, Sargo; Ingman, Kimmo; Alakurtti, Kati; Kaasinen, Valtteri; Virkkala, Jussi; Någren, Kjell; Rinne, Juha O; Scheinin, Harry
Ethanol increases the interstitial dopamine (DA) concentration in the nucleus accumbens (NAcc) of experimental animals, but positron emission tomography (PET) studies using the single-bolus protocol of the [ 11 C]-raclopride competition paradigm have yielded conflicting results in humans. To resolve disparate previous findings, we utilized the bolus-plus-infusion (B/I) method, allowing both baseline and intervention quantification of [ 11 C]raclopride binding during a single 105-minute PET scan, to investigate possible ethanol-induced DA release in nine healthy male subjects. A 25-minute intravenous ethanol (7.6%) infusion, resulting in a 1.3 g/L mean blood ethanol concentration, was administered using masked timing during the PET scan. Automated region-of-interest analysis testing the difference between baseline (40–50 minutes) and intervention (60–85 minutes) revealed an average 12.6% decrease in [ 11 C]raclopride binding in the ventral striatum (VST, P =0.003) including the NAcc. In addition, a shorter time interval from the start of ethanol infusion to the first subjective effect was associated with a greater binding potential decrease bilaterally in the VST ( r =0.92, P =0.004), and the feeling of pleasure was associated with a decrease in binding potential values in both the caudate nucleus ( r =−0.87, P =0.003) and putamen ( r =−0.74; P =0.02). These results confirm that ethanol induces rapid DA release in the limbic striatum, which can be reliably estimated using the B/I method in one imaging session.